An ethernet-based three-phase electricity meter communicating using DNP3 protocol - Figueras, Adrian Meinard R.
Information regarding the electricity consumption of a group of buildings in an area will provide important data which may be used in planning or in developing policies for efficient energy use. One way to obtain this information transfer is through real-time monitoring of the electricity consumption in buildings and utilities from a central data repository such as Supervisory Control and Data Acquisition (SCADA) system. In SCADA system communications, one conventional medium of information transfer is the Local Area Network (LAN). Since most of commercial and industrial buildings have available LAN, an electricity meter that reports to SCADA master in real-time can easily be installed in every building. The meter is implemented with an energy metering integrated chip (IC) which will reduce the size and cost of the meter. Measurements by the IC are then processed by a microcontroller for display and for communications. The information protocol used is the Distributed Network Protocol version 3 (DNP3), a protocol designed for electric utilities due to its efficient error detection, recovery and time-stamping. DNP3 is interfaced with Transmission Control Protocol/Internet protocol (TCP/IP) to efficiently transmit data through Ethernet.